Analisis Sistem Administrasi Pendidikan Dalam Meningkatkan Mutu Sekolah - Deasy Yunita Siregar; Ade Suriyani Nasution; Ardina Khoirunnisa Hasibuan; Azzahra Natasya; Masriyanti Nasution (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This research aims to investigate the role of educational administration systems in enhancing school quality. Employing a qualitative approach, data were gathered through interviews with school administrators, teachers, and educational staff. The analysis revealed that the effective implementation of administrative systems has a positive impact on school performance. This article discusses these findings and provides suggestions for further improvements in educational management at the school level. These findings have significant implications for the development and enhancement of educational quality within the school environment.